The Predictive Value of Inflammation-Related Peripheral Blood Measurements in Cancer Staging and Prognosis - Sylman, Joanna L.; Mitrugno, Annachiara; Atallah, Michelle; Tormoen, Garth W.; Shatzel, Joseph J.; Tassi Yunga, Samuel; Wagner, Todd H.; Leppert, John T.; Mallick, Parag; McCarty, Owen J. T. (Frontiers in Oncology, 2018)
In this review, we discuss the interaction between cancer and markers of inflammation (such as levels of inflammatory cells and proteins) in the circulation, and the potential benefits of routinely monitoring these markers in peripheral blood measurement assays. Next, we discuss the prognostic value and limitations of using inflammatory markers such as neutrophil-to-lymphocyte (NLR) and platelet-to-lymphocyte (PLR) ratios and C-reactive protein (CRP) measurements. Furthermore, the review discusses the benefits of combining multiple types of measurements and longitudinal tracking to improve staging and prognosis prediction of patients with cancer, and the ability of novel in silico frameworks to leverage high dimensional data.